The danger of DIY Do-It-Yourself related full thickness burn injury: Case report during COVID-19 lockdown in Ireland - Aisling Bell; Natasha Christoduolides; Safwat Ibrahim; John Barry O'Sullivan (Elsevier, 2022)
DIY injuries are a common cause of presentation to hospital around the world. During the COVID19 Pandemic there was a significant increase in the number of household injuries. Many of these injuries occur commonly in the home and they presented in increased proportions due to lockdown measures. However during lockdowns people also undertook activities they would normally outsource to skilled professionals which resulted in unique mechanisms of injury. We present the case of a young woman with a delayed presentation of a full thickness burn following the use of an at home laser hair removal device. We will discuss the recent literature on the effects of the pandemic on presentations to emergency services, the surgical management of this injury and its' reconstruction with biodegradable temporising matrix.